Ovine Eimeria infection, OPG and determinants in and around Gondar town, Ethiopia - Senait Belay; Desie Sheferaw (East African Journal of Biophysical and Computational Sciences)
The study aimed to estimate the prevalence of ovine Eimeria infection, assess the associated risk factors, and the intensity of infection. A cross-sectional study design was employed and the study was conducted from November 2017 to May 2018. A total of 422 sheep were selected by systematic random sampling technique, and from these animals, faecal samples were collected and examined for Eimeria oocysts. Of the selected and examined sheep 132 (31.3%, 95% CI=26.8-35.7) were found infected by Eimeria species. The prevalence of Eimeria infection was significant (P <0.05) higher in lambs/young than the adult, in females than males, and in poor body condition than in medium body condition sheep. Moreover, the prevalence of Eimeria infection was significantly (P <0.05) higher in sheep with soft faeces than in normal faeces sheep and semi-intensive than extensive sheep production. The intensity of Eimeria species infection was influenced by the age, sex, body condition, fecal consistency, and production system of sheep (P< 0.05). The overall mean Oocysts per gram of faeces was 2390.6 (95% CI=2007.5-2773.8). The mean OPG was significantly higher in lambs, with poor body conditions and female sheep. In addition, it was higher in sheep with soft faeces and an extensive production system. In conclusion Eimeria species infection was an important problem of sheep production in the study area. Generally, this study's results provided useful information to design and implement appropriate control strategies. Finally, it is recommended that further study identify the species of Eimeria circulating in the areas.